Spirocyclic lactams and curvulinic acid derivatives from the endophytic fungus Curvularia lunata and their antibacterial and antifungal activities - Hilario, Felipe [UNESP]; Polinário, Giulia [UNESP]; de Amorim, Marcelo Rodrigues [UNESP]; de Sousa Batista, Victor [UNESP]; do Nascimento Júnior, Nailton Monteiro [UNESP]; Araújo, Angela Regina [UNESP]; Bauab, Taís Maria [UNESP]; dos Santos, Lourdes Campaner [UNESP] (Elsevier, 2020)
Curvularia lunata, isolated from the capitula of Paepalanthus chiquitensis (Eriocaulaceae), was cultured in potato dextrose broth (PDB) medium. The ethyl acetate extract yielded two new spirocyclic γ-lactams (3 and 4), and five known compounds, namely: triticones E (1) and F (2), 5-O-methylcurvulinic acid (5), curvulinic acid (6) and curvulin (7). Their structures were elucidated by spectroscopic analysis and by the comparison with literature data. Besides, a computational study was used to elucidate the absolute configuration of the C − 3′ in the compounds (3) and (4). The extract and the compounds (1 and 2), (6) and (7) were assayed against gram-positive and gram-negative bacteria and fluconazole-resistant yeast. The triticones (1) and (2) showed good antibacterial activity for Escherichia coli, with a minimum inhibitory concentration of 62.5 μg/mL.
Keywords: Antibacterial activity; Curvularia lunata; Curvulinic acid; Paepalanthus chiquitensis; Spirocyclic lactams